The Lack of Sexual Health Education in Medical Training Leaves Students and Residents Feeling Unprepared. Issue 12 (25th October 2021) - Beebe, Sarah; Payne, Nicolette; Posid, Tasha; Diab, Dinah; Horning, Paul; Scimeca, Alicia; Jenkins, Lawrence C.
ABSTRACT: Background: Despite physicians frequently caring for patients with sexual health issues, only 50% of United States medical schools require formal education in sexual medicine, and there are currently no guidelines pertaining to this with research which found that medical trainees are ill-equipped to provide sexual healthcare. Aim: This study aims to identify areas to improve sexual health training in order to increase physician confidence and competence in evaluating and training patients with sexual health problems. Methods: A prospective survey was sent via REDCap to medical students (n = 190, 68.6%), residents (n = 75, 27.1%), and fellows (n = 11, 3.9%) via a known listserv. Participants (N = 276, ∼15% response rate) were asked to provide demographic information, whether they received sexual health training during medical school and rate their confidence in addressing patients' sexual health concerns. Outcomes: Medical students and residents currently do not receive sufficient education on sexual health and medicine, particularly in fields outside of OB-GYN and Urology, leaving them underqualified and less confident than needed for adequate patient care. RESULTS: 65.6% of trainees reported receiving formal sexual health education, while 13.9% received informal education, and 20.6% received no education during medical school. Although trainees desire to understand a patients' sexual health ( P < .001), only residents in a relevant field (Urology, OB-GYN) felt confident in their ability to assist patients with a sexual health issue ( P = .013). All other trainees lacked confidence in attending to sexual health concerns ( P < .001), regardless of training level ( P > .1). Clinical Implications: More efforts should be made to integrate sexual health education into medical school curriculum. Strengths & Limitations: The strength of this study includes specific evaluation of medical student and resident confidence level with 15 individual sexual health topics. The limitations include that the demographic was regionally confined to the Midwest of the United States and women were more strongly represented among medical students. CONCLUSION: Due to the lack of standardized education, medical trainees (except for Urology and OB-GYN residents) feel unprepared to treat patients with sexual health issues, and medical schools should make sexual health education mandatory.